Evidence based medicine for professional training of physicians: informational and economical aspects - V. A. Fokin; S. I. Karas; T. A. Kalitvyanskaya (Бюллетень сибирской медицины, 2002)
Possible approaches to teaching of methodology of evidencebased medicine in medical university and post degree education of specialists are discussed. There are examined the informational and economical factors leading to raising of medical decisions and introduction of demonstrative approach to medical pr.